Effectiveness Test of Trichoderma harzianum on The Development of Anthracnose Disease (Colletotrichum musae) of Ambon Banana - Yusuf Tayala; Wilhemina Rumahlewang; Abraham Talahaturuson (Agrologia, 2021)
The decrease in the quality of bananas can be caused by the attack of the pathogen Colletotrichum musae which causes anthracnose disease. The use of the antagonist fungus Trichoderma harzianum can be relied upon to control this disease. This study aimed to obtain a more effective level of T. harzianum spore density to suppress the development of anthracnose disease in Ambon bananas. The treatment tested was T. harzianum with five levels of spore density, namely 105, 106, 107,108, and 109 spore/mL, designed using a completely randomized design with five replications. The variables observed were the incubation period and the intensity of the disease. The results showed that the spore density of 109 was effective in suppressing the development of anthracnose disease by inhibiting the incubation period to 3.85 days and suppressing the intensity of the disease to 41.4%.Keywords: Banana, Trichoderma harzianum, Anthracnose, Colletotrichum musae